The Relationship between Conflict Management Styles and Organizational Effectiveness: A Case Study of Herat Municipality - Ataee, Mohammad Asif (International Journal of Scientific Research and Management (IJSRM), 2020)
The general aim of this study is to “examining the relationship between conflict management styles and effectiveness in Herat Municipality in Afghanistan”. The methodology of the research is Descriptive – correlation, and it is practical in terms of aim. The method of sampling in this research is simple random sampling and the sample size is 140 (Female, N= 21 and Male, N= 119) employees of the Herat Municipality. The data gathering tools are the standard questionnaire of conflict management styles and a standard questionnaire of organizational effectiveness. For analyzing data SPSS 22 software is used. According to the results of this study, it can be seen that managers in conflict management in the Herat Municipality use more cooperation and reconciliation strategies. Compromise style also has many effects. The use of these styles signifies the constructive use of conflict. While the use of avoidance style does not affect conflict management, on the other hand, the use of competition style in conflict management has the opposite effect. Since there has been no research on this subject in Afghanistan so far, this research is a novel and new research in this regard that can provide the reader with new information about the topic, especially in Herat province. On the other hand, this research is the beginning of more research in this field for other researchers.